1994
DOI: 10.1111/j.1559-1816.1994.tb00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Jurors' Decisions in Trials of Battered Women Who Kill: The Role of Prior Beliefs and Expert Testimony1

Abstract: The present research explored the influence of four factors on mock jurors' decisions in a homicide trial involving a battered woman who killed her abusive husband: (a) jurors' preexisting beliefs about wife abuse, (b) the presence of expert testimony on the battered woman syndrome, (c) jurors' beliefs in a just world, and (d) gender. Mock jurors listened to a trial involving a woman who had killed her abuser, which either contained expert testimony or did not, and then rendered various judgments about the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 22 publications
7
62
1
Order By: Relevance
“…Beyond these differences in perceptions about IPV and the woman's situation, there were also important gender differences in verdict decisions, whereby female jurors were more likely to vote not guilty on the grounds of self-defense than were male jurors. This significant gender disparity in mock jurors' perceptions about IPV is consistent with prior research (Locke & Richman, 1999;Schuller et al, 1994). Given what it is known about IPV, the cycle of abuse (Walker, 1984), and prevalence rates of IPV (Breiding et al, 2014;Durose et al, 2005), it appears that men's perceptions about IPV continue to be skewed.…”
Section: The Influence Of Juror Gender On Decision-makingsupporting
confidence: 81%
“…Beyond these differences in perceptions about IPV and the woman's situation, there were also important gender differences in verdict decisions, whereby female jurors were more likely to vote not guilty on the grounds of self-defense than were male jurors. This significant gender disparity in mock jurors' perceptions about IPV is consistent with prior research (Locke & Richman, 1999;Schuller et al, 1994). Given what it is known about IPV, the cycle of abuse (Walker, 1984), and prevalence rates of IPV (Breiding et al, 2014;Durose et al, 2005), it appears that men's perceptions about IPV continue to be skewed.…”
Section: The Influence Of Juror Gender On Decision-makingsupporting
confidence: 81%
“…Men perceived more options available to the defendant other than killing, were less likely to believe that the defendants fit the typology of a battered woman, and thought that both women were more in control of their behavior and emotions at the time of the killing. The present research is consistent with previous studies that have found men tend to assign harsher judgments to battered women defendants (Aubrey & Ewing, 1989;Dodge & Greene, 1991;Schneider, 2000;Schuller, Smith, & Olson, 1994;Terrance & Matheson, 2003;Terrance, Matheson, & Spanos, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…The finality that directive support affords would suit those whose cognitive style favors certainty and structure. Further, directive helping may correspond to just‐world beliefs and the victim blaming that these beliefs promote (Schuller et al., 1994). If copers' difficulties are attributed to their own poor judgment or other flaws, there is less reason to endorse the remedies that copers develop, and more reason to impose solutions upon them.…”
Section: Discussionmentioning
confidence: 99%
“…Another cognitive challenge of support is that copers' problems often contradict implicit beliefs in a just world (e.g., Lerner, 1980). In fact, people with high just-world beliefs are more likely to blame victims for their problems (Schuller, Smith, & Olson, 1994).…”
Section: Studymentioning
confidence: 99%